Aging is associated with altered inflammatory, arachidonic acid cascade, and synaptic markers, influenced by epigenetic modifications, in the human frontal cortex - Keleshian, Vasken L; Modi, Hiren R; Rapoport, Stanley I; Rao, Jagadeesh S (Journal of neurochemistry, 2013)
Aging is a risk factor for Alzheimer's disease (AD) and is associated with cognitive decline. However, underlying molecular mechanisms of brain aging are not clear. Recent studies suggest epigenetic influences on gene expression in AD, as DNA methylation levels influence protein and mRNA expression in postmortem AD brain. We hypothesized that some of these changes occur with normal aging. To test this hypothesis, we measured markers of the arachidonic acid (AA) cascade, neuroinflammation, pro- and anti-apoptosis factors, and gene specific epigenetic modifications in postmortem frontal cortex from nine middle-aged [41 ± 1 (SEM) years] and 10 aged subjects (70 ± 3 years). The aged compared with middle-aged brain showed elevated levels of neuroinflammatory and AA cascade markers, altered pro and anti-apoptosis factors and loss of synaptophysin. Some of these changes correlated with promoter hypermethylation of brain derived neurotrophic factor (BDNF), cyclic AMP responsive element binding protein (CREB), and synaptophysin and hypomethylation of BCL-2 associated X protein (BAX). These molecular alterations in aging are different from or more subtle than changes associated with AD pathology. The degree to which they are related to changes in cognition or behavior during normal aging remains to be evaluated.